2001
DOI: 10.1179/026708401101517755
|View full text |Cite
|
Sign up to set email alerts
|

Micro-Impact Testing: A New Technique for Investigating Thin Film Toughness, Adhesion, Erosive Wear Resistance, and Dynamic Hardness

Abstract: A small scale probe testing method has been developed for investigating the behaviour of thin films under dynamic loading conditions. The primary objective of the development was to produce quantifiable techniques that closely simulate the conditions that thin films experience in service. Variations of the technique allow measurements related to: impact wear and adhesion failure, erosive wear resistance, fracture toughness, work hardening, and dynamic hardness. The common element in each variant is the acceler… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
26
0

Year Published

2003
2003
2023
2023

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 50 publications
(26 citation statements)
references
References 5 publications
0
26
0
Order By: Relevance
“…The rate of the crosshead displacement was 0?5 mm min 21 . The optical microscope can be adjusted to observe the coating surface or cross-sectional surface image of the specimen.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…The rate of the crosshead displacement was 0?5 mm min 21 . The optical microscope can be adjusted to observe the coating surface or cross-sectional surface image of the specimen.…”
Section: Methodsmentioning
confidence: 99%
“…The higher fracture toughness means a higher crack propagation resistance, and the higher interfacial shear adhesive strength means a higher crack initiation resistance during the shear stress loading. Various experimental methods such as the pull-off test, 10,11 scratch test, [12][13][14][15] indentation test, [14][15][16][17][18][19] impact test 20,21 and laser ultrasonic testing method 22,23 have been used to evaluate the coating fracture properties and interfacial adhesion properties between the coating and the substrate. However, the methods mentioned above for adhesion measurement have limitations.…”
Section: Introductionmentioning
confidence: 99%
“…Similarly, Bao et al determined that cohesive failure frequently dominated the coating response in impact tests and instead suggested that repeated impact tests be used to assess coating toughness [29]. Recently, instrumented micro/nano scale impact testing has been developed as a potential adhesion test [30]. Since interfacial fatigue can occur in sliding tests, repeated sliding tests have also been proposed as a way of assessing the long-term adhesion of coated surfaces.…”
Section: Interfacial Fatigue Resistance For Long-term Tribological Dumentioning
confidence: 98%
“…After that, researchers found a method to explain the data from tests, and this technique developed rapidly and was applied for estimation of the mechanical properties of various materials [26]. The procedure proposed by Oliver and Pharr [27,28] can be used to deduce the hardness and elastic moduli of various materials, and other indentation-based procedures have been proposed to investigate other mechanical parameters, such as fracture toughness [29,30], fatigue and impact testing [31]. Nowadays, nanoindentation technique is a very powerful method to investigate the mechanical properties of biomaterials [32,33], metals [34], ceramics [35], polymers, and composites [36].…”
Section: Concept Of Nanoindentationmentioning
confidence: 99%